Implementation of Group Discussion Method to Improve Students' Understanding of Asmaul Husana Material at SD Negeri 003 Sei Menggaris - Alias (MANDAILING GLOBAL EDUKASIA, 2025)
This research was motivated by the low level of understanding of the Asmaul Husana (Asmaul Husana) among fourth-grade students at SDN 003 Sei Menggaris, caused by the dominance of monotonous lecture methods. This condition makes students passive, often memorizing without understanding the spiritual meaning of the names of Allah. This study aims to improve student understanding through the application of group discussions. The type of research used was Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Twenty students participated in the study. Data were collected through activity observation, documentation, and learning outcome tests. The results showed significant improvement in each cycle. In the pre-cycle stage, the classical completion rate was only 40%. After the action was implemented in Cycle I, the completion rate increased to 65%, peaking at 90% in Cycle II, with a class average score of 84. In addition to cognitive aspects, student activity and engagement in the learning process also increased dramatically. Students became more confident in expressing their opinions and were able to work effectively in groups. The conclusion of this study is that the group discussion method has proven effective in deepening the understanding of the Asmaul Husana material and is able to create a more interactive, collaborative, and meaningful Islamic Religious Education learning atmosphere for elementary school students.